Deciphering Self-Assembly Mechanisms and Chemical Reactions of Organic Building Blocks on Metal Surfaces by Chemical Bond Imaging - Wiche, Miguel; Justus Liebig University Giessen (My University, 2025)
In recent years, the novel field of on-surface synthesis has been established as one of the main tools for constructing customized, low-dimensional organic nanostructures via bottom-up approaches on atomically flat metal substrates. The self-assembly of the molecular precursors, a process that often serves as pre-step of the on-surface reaction, determines the precise local arrangement of atoms and bonds in neighboring molecules, thus playing a decisive role in product formation. Thereby, intermolecular interactions between hydrogen and fluorine atoms have proven to be a valuable tool to steer molecular alignments. In this work, the mainly unexplored intermolecular hydrogen-fluorine interaction is systematically investigated on inert Au(111) and reactive Cu(111) substrates, using a linear, unilaterally fluorinated 1,2,10,11,12,14-hexafluoropentacene molecule as a model system. In the combined scanning tunneling microscopy and chemical bond imaging study, the local arrangement of hydrogen and fluorine atoms in neighboring molecules is determined in the picometer range and angular variations of a few degrees. While on Au(111) the intermolecular interactions between the molecules are the main contributor to the self-assembly, the higher reactivity of Cu(111) results in different adsorption geometries and molecular arrangements. The highly precise self-assembly study provides new insights into the on-surface interaction of hydrogen and fluorine atoms, thereby highlighting its significance for the field of on-surface synthesis. An on-surface reaction that solely takes place using halogenated precursors is the on-surface Ullmann coupling reaction, which enables the formation of covalent carbon-carbon bonds with the underlying metal surface as a catalyst. However, when applying Ullmann coupling reaction steps, complex self-assembly mechanisms can occur when halogenated precursors interact with the metal surface. Further, cleaved halogens adsorbed on the surface may potentially inhibit the reaction steps. Hence, there is a growing demand for halogen-free precursors for on-surface reactions. Recently, it has been demonstrated that halogen-free (6)Cycloparaphenylene ((6)CPP) molecules are suited to thermally induce a ring-opening polymerization reaction for the synthesis of graphene and biphenylene nanoribbons of confined widths. However, the mechanism of the ring-opening polymerization and the use of cycloparaphenylenes as precursors have not been investigated sufficiently. To contribute to the fundamental understanding of this remarkable reaction, in this thesis we systematically investigate the influence of the ring strain, which decreases with increasing ring size, using a set of cycloparaphenylenes of different sizes ((6)CPP vs. (8)CPP vs. (10)CPP). Our results demonstrate that the ring-opening polymerization is facilitated when using smaller, highly strained cycloparaphenylenes. For larger molecules with lower strain energies, the initial ring-opening is hampered, leading to only partial polymerization for (8)CPP and no polymerization in case of (10)CPP. Additionally, dehydrogenation of individual phenyl rings in intact molecules is observed for (8)CPP and (10)CPP, which further impedes the polymerization reaction.
Entschlüsselung von Selbstassemblierungsmechanismen und Chemischen Reaktionen Organischer Moleküle auf Metallsubstraten mittels Chemical Bond Imaging
Keywords: On-Surface Synthesis; Self-Assembly; Atomic Force Microscopy; Chemical Bond Imaging; Scanning Tunneling Microscopy; ddc:530